PERAN JUSTICE COLLABORATOR DALAM TINDAK PIDANA HUMAN TRAFFICKING PERSPEKTIF HUKUM PIDANA ISLAM - Prasetya, Agung Dwi; Andriyani, Andriyani (Tazir, 2020)
The explanation of the Republic of Indonesia Law No. 21 of 2007 states that human trafficking is an extraordinary crime so that its eradication requires extraordinary efforts, one of which is through a legal breakthrough using the justice collaborator instrument. Therefore, this study will discuss the role of justice collaborators in cases of human trafficking, and will be analyzed from the perspective of Islamic criminal law. The type of research used is juridical normative and uses qualitative data with primary, secondary and tertiary data sources. In this study, the role of justice collaborator is as a criminal act, but not as the main actor who is then used or becomes a witness in an effort to uncover a human trafficking crime. In Islamic law the existence of justice collaborator is allowed because human trafficking is a serious crime. This ability is based on emergency needs. Keywords: justice collaborator, human trafficking, human trafficking